Β-glucosidase supplementation during biomass hydrolysis: How low can we go?. (September 2015) - Pryor, Scott W.; Nahar, Nurun
Abstract: Corn stover was pretreated with dilute sulfuric acid to test the interaction effects of pH, cellulase loading and β-glucosidase loadings on biomass hydrolysis rates. A response surface model was developed showing that β-glucosidase supplementation had limited practical impact on hydrolysis between 0.5 and 2 CBU FPU −1 . The only significant interaction in the model was between pH and β-glucosidase loading but it also had little practical significance. Corn stover and corn cob were used to test the effects of further β-glucosidase reduction. Significant hydrolysis improvements were seen when 0.2 CBU FPU −1 were added but very little improvement was seen for higher loadings. Residual cellobiose concentrations confirmed these findings but suggest that further reductions would have more noticeable negative effects on hydrolysis rates. Results show that β-glucosidase supplementation during biomass hydrolysis can be reduced to between 10% and 20% of typical loadings. Highlights: Optimal hydrolysis pH for dilute acid pretreated corn stover was near 5.0. Hydrolysis rates were similar for β-glucosidase loadings from 0.5 to 2.0 CBU FPU −1 . β-glucosidase loading was reduced to 0.2 CBU FPU −1 with little impact on hydrolysis.